Modeling of the Subsolar Magnetopause Motion Under Interplanetary Magnetic Field Southward Turning - Qiuyu Xu; Binbin Tang; Tianran Sun; Wenya Li; Xiaoxin Zhang; Fei Wei; Xiaocheng Guo; Chi Wang (Space Weather)
Abstract In this study, a new analytical model to describe the time‐dependent subsolar magnetopause motion under interplanetary magnetic field (IMF) southward turning has been developed. This model, based on the scenario of magnetopause erosion due to magnetic reconnection, can be approximated by both linear and non‐linear functions. The linear function is simplified under the assumption of constant magnetopause erosion under southward IMF, and the non‐linear function is derived by assuming that the magnetopause erosion decays exponentially. In the limit of a short time, the non‐linear function is essentially the same as the linear function. By comparing with global magnetohydrodynamic simulations, the linear function performs well within the first 10 minutes, and the error then increases with time. The non‐linear function describes the magnetopause motion more accurately with respect to, and consistent with simulations for a time interval of ∼40 min. This model has also been successfully applied to data‐driven simulations of the 17 March 2015 geomagnetic storm event, suggesting the possible applicability of this model in reality.